The impact of family history on corneal donation and transplantation attitudes: a survey-based study - Okka, Berrin; Belviranli, Selman; Adam, Mehmet; Mirza, Enver; Durduran, Yasemin (Journal of the Pakistan Medical Association, 2024)
Objective: To assess how having a first-degree relative who underwent corneal transplantation influenced people’s attitudes regarding corneal donation and transplantation. Method: The cross-sectional study was conducted between March 15 and April 15, 2023, in the Ophthalmology outpatient department and cornea division of Necmettin Erbakan University Faculty of Medicine Hospital, Konya, Turkiye, and comprised first-degree relatives of patients who had undergone corneal transplantation in group A and controls matched age and gender without family history of transplantation in group B. All the participants filled out a 13-item survey form regarding socio-demographic characteristics and their perspectives on corneal transplantation and donation. Data was analysed using SPSS 20. Results: Of the 263 subjects, 133(50.6%) were in group A; 78(58.6%) females and 55(41.4%) males with mean age 46.5±15.2 years. There were 130(49.4%) subjects in group B; 70(53.8%) females and 60(46.32%) males with mean age 44.3±15.8 years (p>0.05). There were 110(82.7%) participants in group A and 72(55.4%) in group B who knew what corneal transplantation meant (p<0.001). In group A, 81(60.9%) subjects wanted to donate their corneas after death compared to 40(30.8%) in group B (p<0.001). In group A, 108(83.7%) participants stated that a first-degree relative’s corneal transplantation positively affected their view of organ and tissue donation. Conclusion: Individuals whose first-degree relatives had had a cornea transplant showed higher awareness of cornea transplantation and willingness to donate their corneas. Key Words: Cornea transplantation, Keratoplasty, Transplant donors, Awareness, Family medical history.